Method for automatic railway track surface defect classification and evaluation using a laser‐based 3D model. Issue 12 (8th September 2020) - Ye, Jiaqi; Stewart, Edward; Zhang, Dingcheng; Chen, Qianyu; Roberts, Clive
Abstract : Inspection of physical surface defects is a significant concern in many industrial areas. In railway systems, this process mainly includes the detection and classification of defects in rails and wheels, for which laser‐based optical inspection technologies have gradually been applied in the form of 2D profile measurement, benefiting from its high precision and robustness to surface conditions. However, defect classification and evaluation after the initial detection works still rely heavily on human inspectors to make maintenance suggestions. The linear nature of rails makes it possible to increase the dimension of rail measurement data from 2D to 3D by aligning 2D profiles along the rail, from which more comprehensive diagnosis information becomes available. In combination with appropriate artificial intelligence algorithms, this approach can potentially replace human‐dominated defect classification and evaluation work. This study presents a 3D model‐based railway track surface defect classification and evaluation method. A set of geometrical features are extracted from the 3D model of track surface defects to describe a distinguishable pattern for each category of defect. Multi‐class classifiers are then tested and have shown promising results on a group of artificial track surface defects, giving a systemic solution for 3D model‐based automatic track surface defect inspection.